Transforming the treatment of psoriasis to the 21st century: Detecting subclinical therapeutic response to secukinumab using optical coherence tomography as a prognostic indicator. Issue 6 (21st May 2022) - Felice, Skye; Bressler, Moshe Y.; Karim, Raisa; Markowitz, Orit
Abstract: Background: Optical coherence tomography (OCT) is a noninvasive imaging device that scans the skin up to 2 mm in depth. OCT can capture real‐time epidermal thickness (ET) measurements and detect subclinical changes in inflammatory skin diseases like eczema and psoriasis. © 2022 Wiley Periodicals LLC. Objective: To determine if measuring ET with OCT can detect a subclinical therapeutic response in psoriasis treated with the biological therapy, secukinumab (an IL‐17A antagonist). Design: Phase IV, single‐center, open‐label, and single‐arm study. Participants: Twenty‐six consecutive patients with moderate to severe plaque psoriasis. Measurements: Clinical, dermoscopic, and OCT images were obtained at each visit. The clinician measured disease severity with the Investigator's Global Assessment (IGA) and Psoriasis Area And Severity Index (PASI). OCT was used to scan the ET at the center of lesional skin (ET‐L), along the border, and normal skin (ET‐N) on the same body plane; their difference was noted as ΔET. Results: Initially, ET‐L was greater than ET‐N ( p < 0.0001), their differences decreased throughout the study, and there were no significant differences at Week 16 ( p = 0.48). Twenty‐four (92%) patients achieved a 50% reduction in PASI score (PASI50); they had lower ΔET at Weeks 0, 1, 3, 4, and 8 compared to those who did not clear ( p < 0.04). Having a lower ΔET at Week 4 was associated with a shorter time to reach PASI50 ( p = 0.02). Conclusion: ET measurements using OCT can detect an early subclinical response to secukinumab compared to clinical scoring and identify nonresponders as early as 4 weeks.